Educational Process Legislation and Principles and their Use in Student Practice - Norova , Sh.U. (International Journal of Psychosocial Rehabilitation, 2020)
The main goal of the educational reform being carried out in Uzbekistan in the conditions of independence, the harmonious development of the human personality at the center of its model. The article discusses the laws and principles of the educational process. It comments on the research conducted so far in the field of pedagogy. On this basis, methods have been developed to apply these processes in student practice.